Embodied Outdoors Arts-Based Approaches to Mathematical Understanding - Gerofsky, Susan (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2025)
School mathematics instruction remains shaped by pedagogical traditions rooted in nineteenth-century industrial models that privilege static, indoor, and calculation-focused learning. Alternative possibilities for mathematical understanding emerge through embodied, arts-based, and outdoor pedagogies that engage movement, sensory experience, and the living world. Drawing on more than a decade of pedagogical design experiments with educators, preservice teachers, and students, mathematics learning is examined in campus gardens, forests, beaches, and other outdoor environments. Mathematical ideas are developed through bodily movement, artistic practice, and multisensory engagement with land, materials, and seasonal cycles, alongside more familiar forms of mathematical representation. These pedagogical experiments suggest that learning mathematics in and with the more-than-human world can deepen conceptual understanding, foster collaboration, and reconnect mathematics with its historical and ecological roots. Rather than displacing indoor classrooms or paper-and-pencil work, a more balanced mathematics curriculum is advanced—one that integrates embodied and outdoor approaches as complementary ways of knowing across STEM/STEAM education.